THE IMPACT OF THE ROOM TO READ WEBSITE ON STUDENTS' READING SKILLS IN GRADE 1 ELEMENTARY SCHOOL: Pengaruh Website Room To Read Terhadap Kemmpuan Membaca Siswa Kelas 1 SD - aisyatul maslahah; tri susilo; ery rahmawati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The utilization of technology in education is now an important need to improve student literacy. This study aims to (1) determine the effect of using the Room to Read website on the reading ability of grade I elementary school students in Indonesian language subjects, and (2) determine student responses to using this media during the learning process. The research was conducted at SDN Suko 1 Sidoarjo and involved 34 students. It used a quantitative approach of quasi-experimental design. The results showed that there was a significant effect on improving students' reading skills (p = 0.004 <0.05). In addition, students’ responses to this media were very positive with a satisfaction rate of 91%. These results indicate that the Room to Read website is an effective learning media that supports studens early literacy development through a visual and interactive approach.